2018
DOI: 10.1021/acs.bioconjchem.8b00743
|View full text |Cite
|
Sign up to set email alerts
|

Protein Corona Formed from Different Blood Plasma Proteins Affects the Colloidal Stability of Nanoparticles Differently

Abstract: Significant progress in the characterization of protein corona has been made. However, insights on how the corona affects the aggregation of nanoparticles (NPs) and consequent biological identity are still lacking. Here, we examined how the corona formed from four major serum proteins, immunoglobulin G (IgG), fibrinogen (FBG), apolipoprotein A1 (ApoA1), and human serum albumin (HSA), over a range of concentrations affects the aggregation of gold NPs (AuNPs). We found that at physiological pH of 7.4, all four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 116 publications
2
30
0
Order By: Relevance
“…Notably, aggregation was observed for medium size CNPs and large CNP at all plasma concentrations tested, while in the case of small CNPs, aggregation was observed only with 10% of plasma, corresponding to the condition used in in vitro tests, but not in vivo. The latter is in agreement with that recently found on Au nanoparticles by Ho and co-workers [42].…”
Section: Discussionsupporting
confidence: 94%
“…Notably, aggregation was observed for medium size CNPs and large CNP at all plasma concentrations tested, while in the case of small CNPs, aggregation was observed only with 10% of plasma, corresponding to the condition used in in vitro tests, but not in vivo. The latter is in agreement with that recently found on Au nanoparticles by Ho and co-workers [42].…”
Section: Discussionsupporting
confidence: 94%
“…Despite PC being considered as normally responsible for NP colloidal instability, recent studies have demonstrated how the protein amount and their nature have a strong effect on NP stability. In the study by Ho et al, AuNPs were incubated with increasing concentrations of HSA, fibrinogen, immunoglobulin, and ApoA1 (Ho et al, 2018). For all these proteins, the particle aggregation had inverse proportion pattern: at lower protein concentrations, all the proteins increased NP aggregation, but at higher concentrations, the NPs appeared to be stabilized.…”
Section: Np-to-protein Ratiomentioning
confidence: 99%
“…• The presence of cell culture medium can influence PC composition. Bonvin et al, 2017Cox et al, 2018Ho et al, 2018…”
Section: Feature Influence On Np Interactions With Proteins Referencesmentioning
confidence: 99%
“…Ho et al studied how biomolecules influenced the stability of gold nanoparticles and showed that serum proteins at high concentrations stabilized the nanoparticles, whereas lower concentrations enhanced nanoparticle aggregation. Also, immunoglobulins and fibrinogen caused a greater extent of particle aggregation than other studied proteins [ 27 ]. Zhang et al analyzed the effects of different concentrations of nanoparticles on the zeta potential in serum protein media, and demonstrated that 5% fetal bovine serum can cover almost the whole surface of nanoparticles at a concentration below 500 µg/mL.…”
Section: Discussionmentioning
confidence: 99%